2014
DOI: 10.1007/s11284-014-1198-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed bank dynamics in response to an extreme flood event in a riparian habitat

Abstract: A significantly increased water regime can lead to inundation of rivers, creeks and surrounding floodplains-and thus impact on the temporal dynamics of both the extant vegetation and the dormant, but viable soil-seed bank of riparian corridors. The study documented changes in the soil seed-bank along riparian corridors before and after a major flood event in January 2011 in southeast Queensland, Australia. The study site was a major river (the Mooleyember creek) near Roma, Central Queensland impacted by the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…), it is possible that in very fast moving water bodies, such as those of a flood event of January 2011 in Central and South East Queensland (Osunkoya et al . ), or in irrigation cannels and in some river systems, cypselae can be moved vast distances prior to deposition along river banks where they will germinate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), it is possible that in very fast moving water bodies, such as those of a flood event of January 2011 in Central and South East Queensland (Osunkoya et al . ), or in irrigation cannels and in some river systems, cypselae can be moved vast distances prior to deposition along river banks where they will germinate.…”
Section: Discussionmentioning
confidence: 99%
“…Also, anecdotal reports from New South Wales, Australia, indicated that major floods in Queensland during 2010 and 2011 distributed this weed further (Osunkoya et al . ; Mainali et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any sudden or excessive disturbance would cause changes of seed rain, the seed soil bank and plant community. Their relationships also would be changed and the plant community thus would exhibit changes in species composition or even reductions in diversity or species richness (Osunkoya et al 2014;del Castillo and Rios 2008). The dramatic change of the water-level fluctuation pattern in the reservoir resulted in a severe degeneration of seed rain, the soil seed bank and plant community in the hydro-fluctuation zone Lu, Li, Jiang et al 2010;Wang et al 2010;Wu et al 2016).…”
Section: Spatial Distribution Of Seed Rain and Seed Bank And Their Rementioning
confidence: 99%
“…However, when the water-level fluctuation pattern alternates, species composition and the quantity of germinating seeds in the soil seed bank change accordingly (Howard & Wells, 2009;Nicol et al, 2003). Such a change may be due to occasional changes in water-level fluctuation pattern (Lucas et al, 2012;Osunkoya et al, 2014), but when the water-level fluctuation pattern had stabilized, alterations in germination rates of the soil seed bank were observed (Dixon, 2003;Nielsen, Podnar, Watts, & Wilson, 2012).…”
Section: Effects Of Reversal Seasonal Submersion On the Germinationmentioning
confidence: 99%